Atividade antioxidante, composição proximal e lipídica de grãos de amaranto, quinoa e chia - Palombini, Sylvio Vicentin (2012)
The aim of this work were to evaluate proximate composition, total antioxidant activity, as well as total phenolic compounds and flavonoids, and fatty acid quantification by gas chromatography in amaranth, quinoa and chia grains, in natura and defatted grains. Grains had different proximal compositions, being that chia presented the highest values of total protein (23.95±0.45%) and total lipids (32.98±0.26%) whereas, amaranth and quinoa showed the highest values of carbohydrates (57.60±0.03 and 63.42±0.70%, respectively). Concerning fatty acid composition in grain oils, chia proved to be the richest source of omega-3 fatty acids, with 524.67±17.46 mg/g T.L. Amaranth and quinoa grains had the highest oncentrations of oleic acid, with 238.29±4.78 and 231.95±0.82 mg/g T.L., respectively. With respect to linoleic acid, quinoa grains showed the highest oncentration (516.530.56 mg/g T.L.). Chia grains had lower total saturated fatty acids, 85.40±1.74 mg/g T.L., compared to 185.20±3.76 mg/g T.L. in amaranth. It also had the highest sum of polyunsaturated fatty acids, with 701.40±20.77 mg/g T.L Regarding the ratios, chia showed the lowest value for n-6/n-3 ratio (0.33±0.01) and greater value for PUFA/SFA ratio (8.21±0.08). Values of total antioxidant capacity, determined by the method of DPPH free radical capture, was higher in quinoa grains, both in natura and defatted, wich showed an IC50 of 282.99±2.83 and 313.25±10.68 mg/mL respectively. The lower values of antioxidant capacity were observed in amaranth grains, in natura and defatted, with IC50 values of 638.67±67.60 and 715.25±25.38 mg/mL, respectively. With respect of total phenolic compounds, determined by Folin-Cocalteau method, defatted quinoa grains showed the highest values (62.90±3.88 mgGAE/100g), followed by in natura quinoa grains (46.24±4.59 gGAE/100g). The quinoa grains also had the highest values of total flavonoid compounds, with 31.18±0.68 and 26.42±0.51 mgEQ/100g for in natura and defatted grains, respectively. Chia grains had the best lipid profile among the analyzed grains and quinoa was the best source of compounds with antioxidant activity.